2022
DOI: 10.47278/journal.ijvs/2022.165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Presence of Maternal Antibodies on Success of Avian Influenza and Newcastle Disease Vaccinations in Broiler

Abstract: Avian Influenza (AI) and Newcastle Disease (ND) are viral infections that attack poultry worldwide. AI outbreaks in Indonesia were first reported in 2003, which led to the death of millions of birds, while ND is an endemic disease. Vaccination control of these diseases has been carried out, but cases are still being reported in poultry. Therefore, this study aims to determine the effect of age and the presence of maternal antibodies on the success of vaccination using the AI H5N1 and the ND vaccine. It was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…Also, the findings were consistent with those of Wyeth and Cullen (1978), who indicated the possibility of decreasing antibody transfer with age (the mean transfer rate of maternal antibodies against NDV was recorded at just 14.95% with a CV% value of 27.16%). The present study revealed that there were low levels of GMT in female breeders accompanied by low passive maternal antibodies in their progeny, and this agrees with Suardana et al (2022) who recently added that maternal immunity in chickens will be greatly impacted by the females' titer and age. As a result of reduced maternal immunity, chicks from older breeders must be vaccinated at an early age.…”
Section: Effect Of Indian River Broiler Breeder Females' Age On Immun...supporting
confidence: 91%
See 1 more Smart Citation
“…Also, the findings were consistent with those of Wyeth and Cullen (1978), who indicated the possibility of decreasing antibody transfer with age (the mean transfer rate of maternal antibodies against NDV was recorded at just 14.95% with a CV% value of 27.16%). The present study revealed that there were low levels of GMT in female breeders accompanied by low passive maternal antibodies in their progeny, and this agrees with Suardana et al (2022) who recently added that maternal immunity in chickens will be greatly impacted by the females' titer and age. As a result of reduced maternal immunity, chicks from older breeders must be vaccinated at an early age.…”
Section: Effect Of Indian River Broiler Breeder Females' Age On Immun...supporting
confidence: 91%
“…For instance, maternal antibodies against Newcastle disease virus (NDV) reduce the intensity of live vaccines; nevertheless, they also reduce immunity following vaccination (Gharaibeh and Mahmoud, 2013). Suardana et al (2022) reported that there is a necessity for an immediate vaccination for broiler chicks that lack maternal immunity because there will not be interference from maternal antibodies against vaccine antigens. Moreover, a good immune response will be acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Cd has teratogenic consequences in various animals, including chickens, such as appendage deformities, ear abnormalities, and gastrointestinal problems [46,47]. In addition, exposure to Cd can cause eosinophilia, osteoporosis, chronic rhinitis, anemia, and non-hypertrophic emphysema [48,49]. When blood levels of Cd surpass the capacity of metallothionine to bind it, free Cd causes the generation of lipid peroxidases and free radicals, which are detrimental to the kidneys and liver [50].…”
Section: Cadmium On Poultrymentioning
confidence: 99%
“…Cd has teratogenic consequences in various animals, including chickens, such as appendage deformities, ear abnormalities, and gastrointestinal problems ( 55 , 56 ). Additionally, non-hypertrophic emphysema, osteoporosis, persistent rhinitis, anemia, and eosinophilia can all result from Cd exposure ( 57 , 58 ). When the amount of Cd in the blood exceeds the metallothionine ability to bind it, free Cd triggers the production of free radicals and lipid peroxidases, which harm the liver and kidneys ( 59 ).…”
Section: Sources Of Heavy Metal Transmission and Their Impact On Poultrymentioning
confidence: 99%